Therapeutic effect of a Chlamydia pecorum recombinant major outer membrane protein vaccine on ocular disease in koalas (Phascolarctos cinereus). - Sharon Nyari (PLoS ONE, 2019)
Chlamydia pecorum is responsible for causing ocular infection and disease which can lead to blindness in koalas (Phascolarctos cinereus). Antibiotics are the current treatment for chlamydial infection and disease in koalas, however, they can be detrimental for the koala's gastrointestinal tract microbiota and in severe cases, can lead to dysbiosis and death. In this study, we evaluated the therapeutic effects provided by a recombinant chlamydial major outer membrane protein (MOMP) vaccine on ocular disease in koalas. Koalas with ocular disease (unilateral or bilateral) were vaccinated and assessed for six weeks, evaluating any changes to the conjunctival tissue and discharge. Samples were collected pre- and post-vaccination to evaluate both humoral and cell-mediated immune responses. We further assessed the infecting C. pecorum genotype, host MHC class II alleles and presence of koala retrovirus type (KoRV-B). Our results clearly showed an improvement in the clinical ocular disease state of all seven koalas, post-vaccination. We observed increases in ocular mucosal IgA antibodies to whole C. pecorum elementary bodies, post-vaccination. We found that systemic cell-mediated immune responses to interferon-γ, interleukin-6 and interleukin-17A were not significantly predictive of ocular disease in koalas. Interestingly, one koala did not have as positive a clinical response (in one eye primarily) and this koala was infected with a C. pecorum genotype (E') that was not used as part of the vaccine formula (MOMP genotypes A, F and G). The predominant MHC class II alleles identified were DAb*19, DAb*21 and DBb*05, with no two koalas identified with the same genetic sequence. Additionally, KoRV-B, which is associated with chlamydial disease outcome, was identified in two (29%) ocular diseased koalas, which still produced vaccine-induced immune responses and clinical ocular improvements post-vaccination. Our findings show promise for the use of a recombinant chlamydial MOMP vaccine for the therapeutic treatment of ocular disease in koalas.